Pengaruh Kebiasaan Membaca Dan Koleksi Buku Terhadap Prestasi Belajar Mahasiswa Stakpn Ambon - Krislina Pattipeiluhu (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2019)
Education must produce quality human beings who are capable of facing global competition. Therefore, education institutions need to improve the quality of their graduates. In the development of education today both in developed countries and in developing countries, the interest in reading plays a significant role. Success in learning is largely supported by read interest. It is not enough that a study only exerts its power to listen and then memorize it, but it also has to be supported by many personal collections and library support books. By collecting books privately or being good library visitors and being able to use them well, chances are that one's learning achievements will increase. The high culture is fond of reading, resulting in increased interest in reading. The purpose of the study is to know the impact of the reading habits and collection of books on student learning achievements at the STAKPN campus Ambon. The influence of the reading and collection of books on STAKPN Ambon student learning Achievement in tests using existing regression, and begins with knowing the size of the variable donation habits (X1) and book Collection (X2) to variables Learning achievement (Y) is seen that the value of KP = 57%, meaning that the reading habits and books collection gave the contribution to the learning achievement of STAKPN Ambon students by 57% and the remaining 43% is determined by other variablesKeyword: Reading habits, book collections, Learning Achievements